Synthesis of Some New 3-Phenyl-6-methyl-4-substituted styryl coumarins as Antibacterial Agents. - CHAMPANERI, H.R.; MODl, S.R.; NAIK, H.B. (Asian Journal of Chemistry, 2010)
The compounds 3-phenyl-6-methyl-4-substituted styryl coumarins have been synthesized and characterized by elemental analyses and IR spectral studies. Their antibacterial activities against S. aureus and E. coli have also been studied.